COOPERATIVE CHARACTER OF STUDENTS IN VOCATIONAL HIGH SCHOOLS REVIEWED BY EXTRACURRICULAR - Adzro'i, Muhammad; Sridasweni, Sridasweni; Nasution, Jamilah Aini; Asriyana, Asriyana; Siddik, Riesa Rismawati (JOMSIGN: Journal of Multicultural Studies in Guidance and Counseling, 2025)
This text aims to present the results of a survey of the cooperation character of vocational school students in Pekanbaru City based on the extracurricular activities they participate in. The research population was vocational school students and the sample was drawn using simple random sampling technique. The data analysis used is quantitative with descriptive data type. The results found that the character of student cooperation based on the variety of extracurricular activities on average was in the moderate category. Extracurricular activities not only foster students' interests and talents, but also have a positive influence on the character of cooperation and provide students with opportunities to develop strong character.